Prospective, randomized, open-label, blinded end point, two-arm, comparative clinical study to evaluate the efficacy and safety of a Fixed Ayurvedic Regimen (FAR) as add-on to conventional treatment in the management of mild and moderate COVID-19 patients - Arun Gupta; Sasibhushan Vedula; Ruchi Srivastava; Sanjay Tamoli; Narendra Mundhe; D N Wagh; Sanjay Batra; Manoj Patil; Hiren Baburao Pawar; Rajiva K Rai (Wolters Kluwer Medknow Publications, 2021)
Background: The traditional healthcare systems are being avidly looked into in the quest for effective remedies to tackle the menace of COVID-19 pandemic. Objective: This was a prospective randomized, controlled open-label, blinded end point (PROBE) study to evaluate the efficacy and safety of a fixed ayurvedic regimen (FAR) as an add-on to conventional treatment/standard of care (SOC) in the management of mild-to-moderate COVID-19 infection. Methodology: A total of 68 patients were recruited who consumed either FAR + SOC (n = 35) or SOC only (n = 33) for 28 days. Primary outcomes assessed were mean time required for clinical recovery and proportion of patients showing clinical recovery between the groups. Secondary outcomes assessed included mean time required for testing SARS-CoV-2 negative, change in clinical status on World Health Organization (WHO) ordinal scale, number of days of hospitalization, change in disease progression and requirement of oxygen/intensive care unit admission/ventilator support/rescue medication, health status on WHO quality of life (QOL) BREF, and safety on the basis of occurrence of adverse event/serious adverse event (AE/SAE) and changes in laboratory parameters. Results: Patients consuming FAR as an add-on SOC showed faster clinical recovery from the day of onset of symptoms by 51.34% (P < 0.05) as compared to SOC group. A higher proportion of patients taking FAR recovered within the first 2 weeks compared to those taking only SOC. It was observed that 5 times more patients recovered within 7 days in FAR group when compared to SOC (P < 0.05) group. An earlier clinical recovery was observed in clinical symptoms such as sore throat, cough, loss of taste, and myalgia (P < 0.05). Improvement in postclinical symptoms such as appetite, digestion, stress and anxiety was also observed to be better with the use of FAR. Requirement of rescue medications such as antipyretics, analgesics, and antibiotics was also found to be reduced in the FAR group (P < 0.05). FAR showed a significant improvement in all the assessed domains of QOL. None of the AEs/SAE reported in the study were assessed to be related to the study drugs. Further, FAR did not produce any significant change in the laboratory safety parameters and was assessed to be safe. Conclusion: FAR could be an effective and safe add-on ayurvedic regimen to standard of care in the management of mild and moderate COVID-19 patients. CTRI number: CTRI/2020/09/027914.